Geospatial simulation and mapping of climate suitability for oil palm (Elaeis guineensis) production in Peninsular Malaysia using GIS/remote sensing techniques and analytic hierarchy process - Abubakar, Ahmed; Ishak, Mohd Yusoff; Abu Bakar, Aisyah; Uddin, Mohd Kamal; Ahmad, Mohammad Hadi; Abu Seman, Idris; Law, Mei Ching; Ahmad, Afandi; Hashim, Zulkifli (Springer, 2023)
Malaysia is estimated to have cultivated over 5 million hectares of oil palm (Elaeis guineensis), making it the most dominant plantation crop in the country. Malaysia produces about 45% of the world's total palm oil, and it exports about 80% of it. This study aims to identify suitable area for oil palm production in Peninsular Malaysia using remote sensing and GIS techniques and Analytic Hierarchy Process (AHP). Modeling the climate suitability of oil palm production in Peninsular Malaysia using the AHP model of Multi-Criteria Evaluation (MCE) revealed that an annual rainfall rate of approximately (33) was the most important factor contributing to climate suitability. Other contributing factors to climate suitability include number of dry months (17%), annual mean temperature (11%), annual maximum temperature (8%), temperature of the coldest month (7%), slope (5%), elevation (5%), mean annual water deficit (4%), soil texture (4%), soil depth (3%) and coarse fragment (3%) is the least contributing factor. The findings of the study revealed that the current climate in Peninsular Malaysia are suitable for oil palm production. A highly suitable climate is found around Selangor, Kelantan, Perak and Kedah. Climates that are unsuitable are predicted to increase by 5.6% by 2040 and by 5.72% by 2080 from 1.77% in 2020. Climate conditions will become unsuitable for oil palm production along the coast of Pahang and Selangor, and Perlis by 2080. The study recommends the use of the improved variety, appropriate selection of planting area, irrigation where necessary, enhance institutional research on climate and oil palm, communication and availability of academic findings, and the use of technology transfer.